2009
DOI: 10.1098/rstb.2009.0043
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and the origin of the visual retinoid cycle in vertebrates

Abstract: Absorption of a photon by visual pigments induces isomerization of 11-cis-retinaldehyde (RAL) chromophore to all-trans-RAL. Since the opsins lacking 11-cis-RAL lose light sensitivity, sustained vision requires continuous regeneration of 11-cis-RAL via the process called 'visual cycle'. Protostomes and vertebrates use essentially different machinery of visual pigment regeneration, and the origin and early evolution of the vertebrate visual cycle is an unsolved mystery. Here we compare visual retinoid cycles bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 110 publications
0
35
0
Order By: Relevance
“…Based on this hypothesis, deuterostome carotenoid oxygenase proteins outside the RPE65 family do not have isomerohydrolase function and are likely to retain the original oxygenase activity since we did not find any other internal branches that experienced such dramatic acceleration of evolution (Figure 1). Thus, although the Ciona intestinalis BCMOa was initially annotated as RPE65 and was predicted by sequence alignment to be an isomerohydrolase [14], this is not supported by the branch length/time estimates presented in this study, or by our experimental evidence (see below).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Based on this hypothesis, deuterostome carotenoid oxygenase proteins outside the RPE65 family do not have isomerohydrolase function and are likely to retain the original oxygenase activity since we did not find any other internal branches that experienced such dramatic acceleration of evolution (Figure 1). Thus, although the Ciona intestinalis BCMOa was initially annotated as RPE65 and was predicted by sequence alignment to be an isomerohydrolase [14], this is not supported by the branch length/time estimates presented in this study, or by our experimental evidence (see below).…”
Section: Resultsmentioning
confidence: 56%
“…Recently, it was proposed that a prototype of the vertebrate visual cycle is operational in the tunicate Ciona intestinalis [12] when Tsuda and coworkers identified CRALBP, BCMO1 and opsin orthologs in Ciona intestinalis larva and a presumed RPE65 ortholog in adult animals [13]. Though these authors did not test for enzymatic activity of this presumed RPE65 ortholog, they later reported in a review article [14] that they could not detect such activity, though no data was presented. BCMO1 orthologs are also found in arthropods [15] and are essential for chromophore production [16], but this alone does not indicate a vertebrate visual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies (reviewed by Kusakabe et al 2009) suggested that the last common ancestor of tunicates and vertebrates already employed components of the vertebrate visual cycle. In particular, molecular phylogeny and genomic analysis provided evidence for the presence of orthologues of RPE65, CRALBP, and BCMO in the genome of the ascidian Ciona intestinalis, considered to be a close living relative of vertebrates (Takimoto et al 2007).…”
Section: Origin Of the Vertebrate Visual Cyclementioning
confidence: 99%
“…In invertebrate photoreceptors, the pigment is reset to its ground state when it absorbs a second photon that reisomerizes the chromophore from all-trans-back to 11-cis-retinal (54). In contrast, in the vertebrate retina, resetting the visual pigment molecule to its ground state is a complex process called the visual cycle (Fig.…”
Section: Pigment Decay and Regenerationmentioning
confidence: 99%